Neurocysticercosis and pharmacoresistant epilepsy: possible role of calcified lesions in epileptogenesis. Issue 4 (19th September 2020) - Schmid, Marcelo Freitas; Perosa, Sandra Regina; Reyes‐Garcia, Selvin Zacarias; Odreman, Marlene Mayzs; Zetehaku, Ana Carolina; Figueiredo, Nathalia Stela Visona; Duarte, Jeana Torres Corso; Guaranha, Mirian Salvadori Bittar; Mazacoratti, Maria da Graça Naffah; Jr, Henrique Carrete; Centeno, Ricardo Silva; Yacubian, Elza Márcia Targas
Abstract: Neurocysticercosis is a neglected and usually poverty‐related disease of high public importance. The mechanisms by which the calcified lesions cause epilepsy are not known, but have been attributed to residual perilesional gliosis or an inflammatory process. This case shows that an inflammatory response to a calcified granuloma may be associated with the development of epilepsy. The increase in glutamate and kinin B1 (pro‐epileptogenic) receptors added by reduced expression of kinin B2 (anti‐epileptogenic) receptors may explain the chronic epileptogenesis associated with the lesion, corroborating the hypothesis of inflammatory mechanisms involved in the pathophysiology of epilepsy in these patients.